2019
DOI: 10.1002/qua.26118
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for hydrolysis of double six‐membered ring tetraborate anion

Abstract: [B4O5(OH)42−] is a representative borate anion with a double six‐membered ring structure, but there is limited knowledge about the hydrolysis mechanisms of [B4O5(OH)42−]. Density functional theory‐based calculations show that the tetraborate ion undergoes three‐step hydrolysis to form [B(OH)4−] and an ring intermediate, [B3O2(OH)6−]. Other new structures, such as linear trimer, branched tetraborate, analogous linear tetraborate, are observed, but they are not stable in neutral systems and change to ring struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Cheng et al pointed out that when the hydrolysis reaction of Al(OR) 3 occurs, water molecules directly combine with the OR group to form an intermediate in hydrogen bonds 48 . Zhou et al reported that when the hydrolysis reaction occurs between the double six‐membered ring pentaborate ion normalB5normalO6()OH4 and the double six‐membered ring tetraborate ion normalB4normalO5()OH42, water molecules also directly react with borate ions first 34,35 . The anions form hydrogen bonds, and then the water molecules break the bonds again, and the dissociated hydroxyl groups and hydrogen form bonds with the corresponding boron and oxygen, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cheng et al pointed out that when the hydrolysis reaction of Al(OR) 3 occurs, water molecules directly combine with the OR group to form an intermediate in hydrogen bonds 48 . Zhou et al reported that when the hydrolysis reaction occurs between the double six‐membered ring pentaborate ion normalB5normalO6()OH4 and the double six‐membered ring tetraborate ion normalB4normalO5()OH42, water molecules also directly react with borate ions first 34,35 . The anions form hydrogen bonds, and then the water molecules break the bonds again, and the dissociated hydroxyl groups and hydrogen form bonds with the corresponding boron and oxygen, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the intermediate IM1 must absorb energy to reach the transition state. Studies have shown that hydrogen bonds make an important contribution to the change in total energy when the structure of polyborate ions changes during hydrolysis 34,35 . It can be seen that hydrogen bonds play an important role in the energy changes of many reactions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations